Question
upstudy study bank question image url

4) \( \log _{\sqrt{6}}(x-1)+\log _{\sqrt{6}}(x+4)=\log _{\sqrt{6}} 6 \)

Ask by Hamilton Best. in Kazakhstan
Feb 10,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

x = 2

Solution

Рассмотрим уравнение:   log₍√6₎(x - 1) + log₍√6₎(x + 4) = log₍√6₎6 1. Область определения: аргументы логарифмов должны быть положительными. Следовательно,   x - 1 > 0 ⇒ x > 1,   x + 4 > 0 ⇒ x > -4. Общим условием является x > 1. 2. Используем свойство логарифмов: log₍a₎(m) + log₍a₎(n) = log₍a₎(m·n):   log₍√6₎[(x - 1)(x + 4)] = log₍√6₎6 3. При равенстве логарифмов при одинаковом основании (и при положительных аргументах) можем приравнять аргументы:   (x - 1)(x + 4) = 6 4. Раскрываем скобки:   x² + 4x - x - 4 = x² + 3x - 4 = 6 5. Приводим уравнение к стандартному виду:   x² + 3x - 4 - 6 = 0 ⇒ x² + 3x - 10 = 0 6. Решим квадратное уравнение:   Дискриминант D = 3² - 4·1·(-10) = 9 + 40 = 49   Корни:   x = ( -3 ± √49 ) / 2 = ( -3 ± 7 ) / 2   Получаем x = (4)/2 = 2 и x = (-10)/2 = -5 7. Учтем область определения (x > 1):   Корень x = 2 удовлетворяет условию, а корень x = -5 не удовлетворяет. Ответ: x = 2.

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Bonus Knowledge

To solve the equation \( \log _{\sqrt{6}}(x-1)+\log _{\sqrt{6}}(x+4)=\log _{\sqrt{6}} 6 \), we can use the property of logarithms that states \( \log_a b + \log_a c = \log_a(bc) \). This allows us to combine the left-hand side: \[ \log_{\sqrt{6}}((x-1)(x+4)) = \log_{\sqrt{6}} 6 \] Since the logarithms are equal, we can drop the logarithm and set the arguments equal to each other: \[ (x-1)(x+4) = 6 \] Expanding the left side: \[ x^2 + 4x - x - 4 = 6 \] Which simplifies to: \[ x^2 + 3x - 4 = 6 \] Subtracting 6 from both sides gives: \[ x^2 + 3x - 10 = 0 \] Now, we can factor this quadratic equation: \[ (x + 5)(x - 2) = 0 \] Setting each factor to zero results in: \[ x + 5 = 0 \quad \Rightarrow \quad x = -5 \] \[ x - 2 = 0 \quad \Rightarrow \quad x = 2 \] Now we must check if these solutions are within the domain of the original logarithm expressions. The expressions \( x - 1 \) and \( x + 4 \) must both be positive. 1. For \( x = -5 \): - \( x - 1 = -5 - 1 = -6 \) (not valid) - \( x + 4 = -5 + 4 = -1 \) (not valid) 2. For \( x = 2 \): - \( x - 1 = 2 - 1 = 1 \) (valid) - \( x + 4 = 2 + 4 = 6 \) (valid) Thus, the only valid solution is: \[ \boxed{2} \]

Related Questions

Latest Algebra Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy